Dose-response relationships between cigarette smoking and kidney cancer: A systematic review and meta-analysis. (October 2019) - Liu, Xiaoqiu; Peveri, Giulia; Bosetti, Cristina; Bagnardi, Vincenzo; Specchia, Claudia; Gallus, Silvano; Lugo, Alessandra
Abstract: Purpose: We aim to provide the most accurate and updated quantification of the effect of cigarette smoking on kidney cancer risk focusing on dose-response relationships. Methods: We conducted a meta-analysis, using an innovative approach combining an umbrella review and a traditional literature search. Results: Fifty-six original studies were included, providing pooled relative risks (RR) of kidney cancer of 1.39 (95% confidence interval, CI: 1.28–1.51) for current and 1.20 (95% CI: 1.14–1.27) for former compared with never smokers. Kidney cancer risk increased non-linearly with smoking intensity, the RR compared with never smokers being 1.18 (95% CI: 1.11–1.26) for five and 1.72 (95% CI: 1.52–1.95) for 30 cigarettes/day, and increased linearly with smoking duration, the RR being 1.70 (95% CI: 1.10–2.64) after 25 years. The risk linearly decreased with time-since-quitting. Conclusions: Even smoking few cigarettes per day significantly increases kidney cancer risk. Quitting smoking reduces the risk, the earlier the better.